(untitled) (Journal of Pharmaceutical Negative Results, 2022)
Histopathological diagnosis involves examination of slides stained by chemical stains which are health hazard to researchers, technicians and pathologists. This study screened plant based natural stains for histological applications. About 176 test staining solutions were prepared from 11 plant extracts and the staining ability in rat skin tissue was compared with the routinely used Hematoxylin and Eosin (H&E) stain. Punica granulatum, Bixa orellana, Termanalia chebula, Rheum emodi, Rubia tinctorium, Beta vulgaris, Lawsonia inermis, and Tagetes erecta extracts showed more staining intensity. This is the first study to demonstrate the staining ability of Termanalia chebula, Rheum emodi, and Tagetes erecta in biological tissue. Among all plants, Rubia tinctorium and Beta vulgaris showed better staining ability, but lower than H&E. By modifying the concentration, pH, and staining time, we could get better natural stains for histology.